Les Difficultés Des Apprenants Marocains À Mobiliser Les Facteurs Temps Et Espace En Géologie : Cas Des Fossiles - Chmanti-Houari, Imane; Hassani, Mohammed Oudrhiri; Lachkhem, Hassan (European Scientific Journal, ESJ, 2017)
This work aims at diagnosing the Moroccan high school students’ difficulties in perceiving and mobilizing the time and space parameters, particularly through the study of the concepts of fossils. To attain our objective, first, an analysis was carried out on Life and Earth Science programs in Moroccan high school. Then, the results achieved by the Nominal Group Technique (NGT) have enabled us to elaborate a questionnaire related to the concept of fossils. These investigation tools affirm that the students have difficulties in assimilating and mobilizing the time and space parameters, particularly while overvaluing the time factor at the expense of the space one, a confusion in the mobilization of the temporal scales and inability to imagine the succession in time and space of the different stages of the fossilization. To reduce the difficulties faced by the learners, we suggest some pedagogical solutions.